Efektifitas Penggunaan E-Bekal Sebagai Uang Saku Elektronik di Pesantren - Fathma Hanum; Saiful Bakhri; Fathor Rozi (Tasharruf : Journal of Islamic Economics and Business, 2022)
E-bekal is electronic pocket money used in the Nurul Jadid Islamic boarding school environment. The emergence of e-bekal is the answer to several problems. Many students from out of town and even abroad have difficulty receiving pocket money from their parents, uncontrolled student pocket money, and many cases of losing money. The emergence of e-bekal as an answer to the problem certainly has a practical value because in solving the problem, there must be some obstacles that will be faced so that researchers feel the need to conduct research related to the effectiveness of using e-supply as electronic pocket money in Islamic boarding schools. This study wants to examine how effective the presence of e-bekal among students as direct users of e-bekal is. The method used in this research is descriptive and quantitative with the type of case study. The results of this study conclude that the use of e-Bekal is still less effective because there are still many students who have not felt the benefits that can be supposed in using e-bekal, even though they tend to be less inclined to use e-bekal as a medium of payment because there are still many obstacles in its use, so that need a lot of system improvements and also upgrade the e-stock software it self.